The government valuation of Ireland: an examination of its authority as a standard of value - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1893)
The first act for the valuation of Ireland was passed in the year 1826 (7 Geo. IY. cap. 62). It was intended to form the basis of rating for county purposes only, its object being, according to the preamble, "the more equal levying of county cess charges and grand jury rates upon the several baronies, parishes, and other divisions of land, within the several counties of Ireland." Under this statute a Commissioner of Valuation was appointed. Mr. Griffith (afterwards Sir Eichard Griffith) was the first to fill the post, and this, and all subsequent valuations of Ireland were carried out under his directions.
Read Tuesday, 22nd November, 1892
Keywords: Property valuation; Rental calculation; 314.15